1997
DOI: 10.1007/s004360050343
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface carbohydrates of Entamoeba invadens

Abstract: Cell-surface carbohydrates of Entamoeba invadens trophozoites were analyzed using (a) a panel of highly purified lectins specific for molecules containing N-acetylglucosamine or sialic acid, N-acetylgalactosamine, galactose, mannose-like residues, and fucose; (b) Escherichia coli K-12 with mannose-sensitive fimbria; (c) enzymatic digestion; and (d) scanning electron microscopy. The presence of galactose (D-Gal) and N-acetylgalactosamine (D-GalNAc) was detected in the amoeba. Previous trypsinization induced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The specific avidity exhibited by FITC-lectins employed is well documented (Van Damme et al 1998), hence the nature of cyst and trophozoite carbohydrate cell surface exposure, rather than mere carbohydrate composition alone may be elucidated. In contrast with the trophozoites of Entamoeba invadens (Ribeiro et al 1997), acanthamoebal trophozoites investigated showed somewhat less avidity for galactose-and N-acetylgalactosamine-specific lectins compared with Nacetylglucosamine-specific WGA, potentially indicative of their different surface composition and nature. Acanthamoebal cysts and trophozoites, although their cell wall and plasma membrane composition differs greatly, also show some degree of similarity in cell surface carbohydrate exposure, as lectins specific for N-acetylglucosamine, N-acetylgalactosamine and mannose/glucose readily bind to both their surfaces.…”
Section: Fitc-lectin Concentration and Binding By Trophozoites And Cystsmentioning
confidence: 79%
See 3 more Smart Citations
“…The specific avidity exhibited by FITC-lectins employed is well documented (Van Damme et al 1998), hence the nature of cyst and trophozoite carbohydrate cell surface exposure, rather than mere carbohydrate composition alone may be elucidated. In contrast with the trophozoites of Entamoeba invadens (Ribeiro et al 1997), acanthamoebal trophozoites investigated showed somewhat less avidity for galactose-and N-acetylgalactosamine-specific lectins compared with Nacetylglucosamine-specific WGA, potentially indicative of their different surface composition and nature. Acanthamoebal cysts and trophozoites, although their cell wall and plasma membrane composition differs greatly, also show some degree of similarity in cell surface carbohydrate exposure, as lectins specific for N-acetylglucosamine, N-acetylgalactosamine and mannose/glucose readily bind to both their surfaces.…”
Section: Fitc-lectin Concentration and Binding By Trophozoites And Cystsmentioning
confidence: 79%
“…In turn, FITC-lectin avidity of Acanthamoeba and Naegleria strains differed between morphological forms, species and pathogenic or nonpathogenic strains of the same species (Bose et al 1989). More sophisticated Entamoeba studies have not only demonstrated further the experimental potential of fluorescent lectins in elucidating protozoan cell surface nature and dynamics (Ribeiro et al 1997), but also the natural role of lectins as encystation-specific glycoproteins in cyst-wall maturation (Frisardi et al 2000). The studies outlined below employ the techniques of flow cytometry and a panel of FITC-lectins and concepts developed from ligand-receptor studies, to characterize Acanthamoeba polyphaga cyst and trophozoite lectin avidity, hence surface carbohydrate nature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Vommaro et at. 1997, Feng & Woo 1998, Entamoeba invadens (Ribeiro et al 1997), Glugea plecoglossi (Kim et al 1999), Leishmania spp. (Grogl et al 1987, Jaffe & McMahon-Pratt 1988, Sphaerospora sp.…”
Section: Abstract: Lectins · Ichthyophthirius · Immobilization · Invmentioning
confidence: 99%